2011
DOI: 10.1002/ijc.25794
|View full text |Cite
|
Sign up to set email alerts
|

A pooled analysis of 14 cohort studies of anthropometric factors and pancreatic cancer risk

Abstract: Epidemiologic studies of pancreatic cancer risk have reported null or nonsignificant positive associations for obesity, while associations for height have been null. Waist and hip circumference have been evaluated infrequently. A pooled analysis of 14 cohort studies on 846,340 individuals was conducted; 2,135 individuals were diagnosed with pancreatic cancer during follow-up. Study-specific relative risks (RRs) and 95% confidence intervals (CIs) were calculated by Cox proportional hazards models, and then pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
179
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(205 citation statements)
references
References 37 publications
(80 reference statements)
15
179
3
8
Order By: Relevance
“…However, with a larger number of studies, we also found significant associations among both men and women and among American, European and Asian studies and there was no evidence of a difference between the summary estimates for these subgroups, confirming the importance of body weight control for pancreatic cancer prevention in diverse populations and among both genders. Two pooled analyses (64;65) and a meta-analysis (3) have previously reported somewhat stronger associations among women than among men, while our meta-analysis and another pooled analysis (66) showed similar results in men and women. The difference between our findings and the previous analyses may relate to the larger number of studies now available and therefore more statistical power to detect an association also among men.…”
Section: Discussionsupporting
confidence: 78%
“…However, with a larger number of studies, we also found significant associations among both men and women and among American, European and Asian studies and there was no evidence of a difference between the summary estimates for these subgroups, confirming the importance of body weight control for pancreatic cancer prevention in diverse populations and among both genders. Two pooled analyses (64;65) and a meta-analysis (3) have previously reported somewhat stronger associations among women than among men, while our meta-analysis and another pooled analysis (66) showed similar results in men and women. The difference between our findings and the previous analyses may relate to the larger number of studies now available and therefore more statistical power to detect an association also among men.…”
Section: Discussionsupporting
confidence: 78%
“…As mentioned, several studies present results showing an increased risk of pancreatic cancer with increasing BMI,13, 21, 22, 23 which has not been observed in the MDCS, neither in men nor in women 42. Still, adipose tissue is also known to produce estrogens, thus suggesting it may play a protective role as well.…”
Section: Discussionmentioning
confidence: 93%
“…Tobacco smoking,4, 5, 6 high age4, 7, 8 and heredity9, 10 seem to be the only truly validated risk factors for pancreatic cancer. Several other risk factors have been investigated, and numerous studies claim a significant impact of diabetes,11, 12, 13 pancreatitis,14, 15, 16 alcohol17, 18, 19, 20 and body mass index (BMI)13, 21, 22, 23; however, no consensus has yet been reached.…”
mentioning
confidence: 99%
“…Postmenopausal obesity is a predictor of fatal breast cancer [9] and increased risk for endometrial cancer [10] and ovarian cancer [11]. Much like the other cancers, obesity also increases pancreatic cancer risk [12,13]. Other studies indicate, however, that weight lossin particular that accompanying with gastric bypass -is associated with reduced cancer risk when compared to those without surgery [14].…”
Section: Introductionmentioning
confidence: 99%